PENGARUH KEPEMIMPINAN, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI THE GOODS DEPT - Aris Budiono; Sigit Dani Nugroho; Aditya Muhammad Luqman (Human Capital Development, 2020)
Purpose- This research was conducted in order to find out whether leadership, compensation and motivation influence the employee performance at The Goods Dept Design/methodology/approach- In this sample research respondents used were The Goods Dept employees consisting of 63 respondents, by saturated technique. The analysis technique uses multiple linear regression. Findings- Base on analysis, it can be concluded that simultaneously leadership (X1), compensation (X2), and motivation (X3) influence the employee performance (Y). It was also concluded that partially (individual) leadership and compensation influence the employee performance, but motivation is not influence the employee performance. The result shows that compensation have the most impact significantly on employee performance at The Goods Dept